Menstrual cycle disruption occurs at any duration of Depo Medroxyprogesterone Acetate usage - Muhammad Haritsyah Rahmadana; Ulya Uti Fasrini; Bobby Indra Utama; Abdiana .; Nurhayati . (Jurnal Sains Farmasi Dan Kesehatan, 2026)
This study investigated the relationship between the duration of Depo Medroxyprogesterone Acetate (DMPA) contraceptive use and menstrual cycle disturbances among users at the Nanggalo Community Health Center in Padang, West Sumatra. An observational analytical approach with a cross-sectional design was employed, involving 56 female respondents selected through simple random sampling. Data collection included the PSS-10 questionnaire to exclude participants with high stress levels and an interview questionnaire to assess menstrual cycle disturbances. Analysis using the Chi-square test revealed that the majority of respondents (62.5%) had used DMPA for more than 24 months. The most common menstrual disturbance reported was amenorrhea (69.6%), followed by oligomenorrhea (8.9%) and polymenorrhea (7.1%). Statistical analysis showed no significant association between the duration of DMPA use and the occurrence of menstrual disturbances (p=0.876). These findings suggest that the length of DMPA use does not significantly influence menstrual cycle changes among users in this setting, and they may serve as useful educational material for healthcare providers and considerations for individuals choosing DMPA as a contraceptive.